Effect of the Alkalized Rice Straw Content on Strength Properties and Microstructure of Cemented Tailings Backfill - Wang, Shi; Song, Xuepeng; Wei, Meiliang; Liu, Wu; Wang, Xiaojun; Ke, Yuxian; Tao, Tiejun (Frontiers in Materials, 2021)
The tailings and rice straw are waste by-products, and the storage of tailings on the ground or the burning of rice straws will seriously damage the ecological environment. In this paper, the effect of different contents of alkalized rice straw (rice straw was alkalized with 4 % NaOH solution, ARS) on the mechanical properties of cemented tailings backfill (CTB, ARSCTB) was studied through experiments. The results indicated that (i) the uniaxial compressive strength (UCS) of the ARSCTB could be improved by ARS. However, with the ARS content increased from 0.1 to 0.4 wt%, the UCS showed a monotonous decreasing trend. The UCS improvement effect was best when ARS content was 0.1 wt%, and at 7, 14, and 28 d curing ages, the UCS increased rate was 6.0, 8.3, 14.7 % respectively. (ii) The tensile strength of the ARSCTB was generally higher than that of the CTB, and was positively correlated with ARS content. The tensile strength increase rate was 24.1 ~ 34.2 % at 28 d curing age. iii) Scanning electron microscopy (SEM) test indicated that ARS was wrapped by cement hydration products, which improves its connection with ARSCTB matrix. The ARS performed a bridging role, inhibited cracks propagation, and provided drag or pulling force for the block that is about to fall off. Therefore, the mechanical properties of the ARSCTB were enhanced. However, under high ARS content, the inhibition of ARS on hydration reaction and the overlap between ARS were not conducive to the improvement of the UCS of the ARSCTB. iv) The post-peak residual strength and integritory effect of the ARSCTB were greater. It is recommended to add 0.1 ~ 0.2 wt% ARS to the backfill with high compressive strength requirements such as the empty field subsequent filling mining method and the artificial pillar. 0.3 ~ 0.4 wt% ARS is incorporated into backfill with high tensile strength requirements such as high-stage filling with lateral exposure and artificial roof.